The Islamic Emirate Of Afghanistan 1.0: A Study on Islamic Government Practices under the Taliban 1996- 2001 - Ridwan Rosdiawan; Dwi Surya Atmaja; Khan Pacha (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The Taliban group managed to return to power in Afghanistan after the departure of the international coalition forces led by the United States and the collapse of President Ashraf Ghani's government in August 2021. Their determination to revive the Islamic Emirate of Afghanistan has raised global public fears that the Taliban will repeat the practice of a hardline Islamic government as previously practiced. they have implemented in the first five years of their leadership phase. What was the pattern of the Islamic government of the Taliban version that was implemented in 1996-2001? By analyzing the content of data sourced from documents in the form of official political texts, news reports, journal articles, and books circulating in the context of the time, this paper presents an explanation that reveals why the pattern of Islamic rule of the Taliban is the anti-thesis of the ideal model of government adopted. the majority of the international community. Instead of strengthening democratization and upholding human rights, the Taliban implemented many policies that curbed the basic freedom rights of the Afghan people in the fields of education, livelihood, and social and political affairs based on adherence to religious dogmas.